PENGGUNAAN GAMES SMARTPHONE DAN PENGARUHNYA PADA ANAK USIA SEKOLAH (SD) DI PERUMAHAN BAKTI KARYA ASRI TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Risman Efendi; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This thesis is proposed to qualify for a bachelor's degree in Sociology. With the title "The Use of Smartphone Games and Its Influence on School Children (SD) in Bakti Karya Asri Tarai Building Mine Sub-District Kampar District." The use of game games is very mushroom among school-age children (SD), the use certainly has a certain influence on the behavior social child. In the game game there are aspects of the type of game play, game time, and the cost used. While social behavior there are aspects in the form of rebellion, aggression, disputih / bertengkar, competition, behavior in power, selfish. This study aims to determine the use of Smartphone Games and its effect on the social behavior of school-age children (SD) in Bakti Karya Asri Housing Tarai Bangun Kecamatan Tambang Kabupaten Kampar.Teori used in this study is social behavior. The research location is Bakti Karya Asri Tarai Bangun housing, Tambang Sub District, Kampar regency. While the method used in this research is descriptive quantitative. The population of this study as many as 26 respondents while the sample used as many as 26 parents. Sampling techniques used are accidental sumple and data collection using interviews, questionnaires and documentation. The results of research in the form of the influence of social behavior of children using game games include the behavior of many children who always want to win in game games, it turns out the behavior of many children feel offended or disturbed by the attitude and behavior of other children, it turns out that many children's behavior against the parents, the behavior of many children who at any time want to fulfill their own interests, it turns out the child's behavior is not always always behind the back both physically (nonverbal) and with the words (verbal), in terms of behavior in power is the behavior of children does not always dominate the social situation. Keywords: Smartphone Games, Social Behavior